What made California the Golden State? : life during the gold rush - Khor, Shing Yin; Gray, Kass (New York : Penguin Workshop, 2024)
"Explore the Gold Rush from the perspective of William Miller and Henry Garrison, two miners in the Sierra Nevada region, and uncover the often unrelenting conditions of the California gold mines. A story of community, determination, and the search for the American Dream, this graphic novel invites readers to immerse themselves into what life was really like during this pivotal period in American history--brought to life by a gripping narrative and vivid full-color illustrations that jump off the page"--
Includes bibliographical references.
Ages 8-12
Keywords: Frontier and pioneer life -- California -- Juvenile literature; Frontier and pioneer life -- California -- Juvenile literature; California -- Gold discoveries -- Juvenile literature; California -- History -- 1846-1850 -- Juvenile literature; California -- Gold discoveries -- Juvenile literature; California -- History -- 1846-1850 -- Juvenile literature; Graphic novels